آيات الصيام الواردة في سورة البقرة: دراسة مقارنة لأقوال العلماء - القحطاني، فاطمة بنت جبران بن مرعي (جامعة الأزهر - كلية أصول الدين والدعوة بالزقازيق, 2018)
الحمد لله رب العالمين، والصلاة والسلام على رسول الله صلى الله عليه وسلم، وعلى آله وصحبه وسلم تسليما كثيرا، وبعد: فقد يسر الله تعالى أن أكتب هذا البحث المتواضع، والذي تناولت فيه آيات الصيام الواردة في سورة البقرة، جامعة من خلاله لأنواع التفسير، من التفسير الموضوعي، والتفسير التحليلي، والتفسير المقارن. حيث وضعت عناوينه مستمدة من التفسير الموضوعي، وقسمت الآيات باعتباره، ثم بدأت بدراسة الآيات دراسة تحليلية، كتبت فيها ما يسر الله من تفسير لغريب وقراءات وبلاغة، وفسرتها تفسيرا إجماليا ميسرا، وختمت بالفوائد التي رأيت من كل آية، ثم ختمتها بدراستها دراسة مقارنة فقهية جامعة بين أقوال المفسرين والعلماء في المذاهب الأربعة، ورجحت في كل مسألة ذكرتها بما رأيته صوابا، فإن أصبت في ذلك فمن الله وحده، وإن أخطأت فمن نفسي والشيطان. وقد اتبعت في كتابة البحث المنهج العلمي الصحيح، من كتابة للآيات بالرسم العثماني، وتخريج الأحاديث، وتوثيق النصوص، ومراعاة قواعد الإملاء والنحو، وغيرها من المناهج العلمية في كتابة البحث العلمي.
Allah helps me to write this research. I have dealt with fasting verses in Surat El-Baqara. I have gathered some sorts of interpretations, the objective, the analyzing and the comparative ones. I have put its headlines according to the objective interpretation, also divided the verses by considering it I have started studying the verses by considering it. I have started studying the verses in analyzing methodology. I have written the interpretation, tongues of reciting, and figures of speech. I have introduced a wholly vacillated interpretation. I have concluded by benefits of each verse. I have finished by a comparative jurisprudent study followed a method of the four- parties in jurisprudence. I have chosen the righteous matter in each case. If I am rightful, that is the grace of Allah alone. If I do mistake, that is myself and the devil. I have followed the right scientific method in writing the research. I have written the verses by ottoman script of writing. I have testified the Hadiths. I also have documented the texts. I have kept the right methods of dictation and grammar, and all the scientific methods in writing the research.
Keywords: القرآن الكريم -- سورة البقرة -- آيات الصيام -- تفسير القرآن -- الأحكام الفقهية